Effects of different types of fruit bags on peel color and fruit quality in Zijinhong No. 2 peach - YOU Shuanghong; SHI Wenjing; CHEN Yuanping; WEI Zhaoxin; ZHOU Guangwen; LIU Jiahong; YAN Chongxi; HAN Guohui (Guoshu xuebao)
[Objective] In recent years, nectarines have become increasingly popular among consumers due to their bright color, smooth skin without fuzz, and convenient consumption. A large number of nectarine varieties have been introduced to Chongqing. Zijinhong No. 2 is an excellent variety cultivated by the Jiangsu Academy of Agricultural Sciences. This cultivar is characterized by smooth glabrous skin with a yellow ground color and vibrant red blush, and the flesh is firm and melting, with minimal fiber, a sweet flavor and aromatic quality. In 2017, this nectarine variety was introduced and planted in the Bishan district by Chongqing Academy of Agricultural Sciences. Through years of continuous observation and trials, it was found that this variety performed well in Chongqing and was suitable for local cultivation. However, the growing period of Zijinhong No. 2 nectarine lasts from April to June, which coincides with the rainy season or heavy rainfall periods, leading to severe disease occurance and significantly affecting the fruit quality. So this study investigated the effects of different types of fruit bags on the peel pigments and fruit quality, aiming to identify the suitable fruit bag type for early-ripening nectarines in the Chongqing region. [Methods] Using Zijinhong No. 2 nectarine as the subjects for the study, nectarine fruits were bagged approximately 30 days after flowering with the following treatments: white single-layer bags (Treatment Ⅰ), yellow single-layer paper bags (Treatment Ⅱ), Double-layer paper bags with a yellow outer layer and white inner layer (Treatment Ⅲ), and double-layer paper bags with a yellow outer layer and black inner layer (Treatment Ⅳ), with an unbagged group serving as the control (CK). The light transmittance rates with different treatments ranked as follows: CK>Ⅰ>Ⅱ>Ⅲ>Ⅳ. Fruit samples were collected at 60 (S1), 70 (S2) and 80 (S3) d after flowering (DAF), respectively. After sampling, the single fruit mass was measured using an electronic balance, the longitudinal, transverse, and lateral diameters of the fruit were measured using a vernier caliper, and the red-green color difference a* value, yellow-blue color difference b* value and light L* value were detected by the color difference meter. The physiological indicators including the chlorophyll, carotenoid and anthocyanin contents, the total and each types of soluble sugar contents, and total and each types of organic acids contents were measured following the corresponding physiological experimental method, respectively. Correlation analysis, principal component analysis (PCA) and heat map cluster analysis were employed to comprehensively evaluate the fruit quality at each time point with various bagging treatments. [Results] Under bagging conditions, the single fruit mass showed no significant difference at S1 and S2 stages compared to CK. However, at the stage of fruit maturity (S3 stage), Treatment Ⅰ significantly increased the single fruit mass by 26.10% compared to CK, while treatments Ⅱ and Ⅲ increased by 4.72% and 3.64%, respectively, though these differences were not statistically significant. In contrast, treatment Ⅳ led to a 3.30% reduction in single fruit mass, but the difference was still not significant. Bagging treatments had no significant effect on improving fruit shape. The effects of different bagging treatments on longitudinal and transverse diameters were different. Treatment Ⅳ significantly increased the fruit shape index by 11.24%, while the other three bagging treatments showed no significant difference compared to the control. Bagging improved the appearance and coloration of fruits, effectively. Compared with CK (control) at S3 stage, except for treatment Ⅰ, the other three bagging treatments significantly reduced the red-green color difference a* value (by 5.75%, 10.76% and 32.74%, respectively), increased the light L* value (by 23.03%, 33.99% and 36.27%, respectively), and enhanced the hue angle H value (by 11.59%, 16.53% and 38.08%, respectively). All four bagging treatments significantly increased the yellow-blue color difference b* value (ranged from 6.90% to 31.64%) and color saturation C value (ranged from 4.36% to 6.02%) at the fruit ripening stage. Bagging generally and significantly inhibited the synthesis of chlorophyll and anthocyanins in fruit peels during the ripening stage (S3). Under the four bagging treatments conditions, chlorophyll contents decreased by 29.20%, 37.55%, 71.36% and 91.08%, respectively; while anthocyanin contents declined by 40.55%, 48.72%, 64.31% and 75.45%, respectively. Different types of fruit bags showed varying effects on carotenoid contents: treatments Ⅰ and Ⅱ significantly increased carotenoid contents in the fruit peel by 37.18% and 22.68%, respectively; whereas treatments Ⅲ and Ⅳ resulted in reductions of 1.08% and 8.05% in carotenoid contents in peels during the ripening stage, though these differences were not statistically significant. Treatment Ⅰ significantly increased the total sugar content by 7.04% and reduced the organic acid content by 6.40%. The other three bagging treatments significantly decreased the total sugar contents by 8.07%, 14.62% and 22.92%, respectively; while they increased the organic acid contents by 0.62%, 27.69% and 32.44%, respectively. Bagging had no significant effect on the relative proportion of sugar and acid components in fruits. Among the sugar components, sucrose content was the highest, followed by fructose, and then fructose and glucose, with sorbitol content being the lowest. Among the acid components, quinic acid content was the highest, followed by isocitric acid and malic acid, with citric acid content being the lowest. The correlation analysis showed that the appearance quality indicators such as fruit mass, longitudinal diameter, transverse diameter, lateral diameter, fruit shape index, red-green color difference, yellow-blue color difference, color saturation and hue angle were generally positively and/or negatively correlated with the internal quality indicators such as chlorophyll, carotenoids, anthocyanins, soluble solids, soluble sugars, sucrose, glucose, fructose, sorbitol and titratable acid contents. This indicated that there was a certain correlation between the appearance quality and the internal quality of fruits. Two principal components were obtained using PCA analysis with a cumulative variance contribution rate of 87.459%. The color saturation C value, the content of chlorophyll, the longitudinal diameter, the transverse diameter and the lateral diameter were the key indicators for the comprehensive quality evaluation for nectarine fruit. The comprehensive evaluation model was established: F=0.506 F1+0.494 F2. Based on this analysis, the comprehensive scores of nectarine fruit quality with different bagging treatments at various developmental stages were calculated and ranked as follows: Treatment Ι at S3 stage>CK at S3 stage>Treatment Ⅱ at S3 stage. [Conclusion] The white single-layer paper bag is suitable for the Zijinhong No. 2. The results provide a support and reference for the selection and proper use of fruit bags for early-ripening nectarine in Chongqing.